Summarizing the Evidence Base for Palliative Oncology Care: A Critical Evaluation of the Meta-analyses. (April 2020) - Rogers, James L; Perry, Laura M; Hoerger, Michael
Background: Palliative care is a specialized approach to symptom management that focuses on supporting patients' physical and psychological quality of life throughout the disease course. In oncology, palliative care has been increasing in utilization. The evidence base for such care is also growing through the use of randomized controlled trials (RCTs). In this review, we aim to integrate the findings from 4 meta-analyses of palliative oncology care RCTs to examine the impact of palliative care on physical and psychological quality of life and survival. Method: We considered 4 meta-analyses of palliative oncology care RCTs, which each used slightly different methodologies and analyses. Two of the meta-analyses included both outpatient and inpatient populations, whereas the remaining meta-analyses focused specifically on outpatient palliative oncology care. Results: All 4 meta-analyses reported a robust quality of life advantage for patients randomized to receive palliative care. Two meta-analyses identified a survival advantage, whereas the other 2 detected no survival differences. In 1 meta-analysis that examined high-quality RCTs of outpatient palliative oncology care, it was found that an increased survival probability for palliative care, compared with standard of care, was confined to 6- to 18-month follow-up. Conclusions: There is a growing evidence base for palliative oncology care, as highlighted by the 4 meta-analyses considered. Such care successfully improves both physical and psychological quality of life for patients with serious illnesses, especially cancer. Clinicians should educate patients and their caregivers about the findings of these meta-analyses. Finally, governmental policies should focus on increasing palliative care access.